Laba Akuntansi sebagai Sumber Informasi Pengembangan Usaha - Sabaruddin Chaniago; Saparuddin Siregar (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
Accounting profit is a basic source of information for current and potential users in business decision-making procedures for small, medium, and large businesses. The company's financial statements are intended for external users, but also for internal users. The question, however, is the extent to which employers use the information obtained in the manner they do to achieve management objectives. The findings in this study indicate that the use of accounting profit as a consideration for business development can increase business success. Furthermore, by using information obtained from financial statements, it provides an analysis of how accounting profit affects business expansion, especially through cost investment. Keywords: financial statements, accounting profit, business expansion